Cerebral Blood Flow in Sturge-Weber Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Regional cerebral blood flow during seizure activity, measured by transcranial Doppler sonography, and SPECT were studied in three infants with Sturge-Weber syndrome (SWS), during work-up for possible epilepsy surgery at Great Ormond Street Hospital and The Institute of Child Health, London, UK.